Naringenin impairs mitochondrial function via ROS to induce apoptosis in tamoxifen resistant MCF-7 breast cancer cells - Lauren A. Eanes; Mayar Eldeeb; Darrell Storholt; Yashomati M. Patel (PLoS ONE, 2025)
Breast cancer is the second leading cause of cancer deaths among women. While tamoxifen, a commonly used drug therapy in breast cancer patients, is effective, many patients acquire tamoxifen resistance. Therefore, it is essential to identify alternative or combination therapeutics for the treatment of breast cancer. Naringenin, a naturally occurring flavonoid, has been reported to elicit antioxidant, anti-proliferative, and pro-apoptotic effects in cancer cells. The current study aimed to identify the mechanism by which naringenin induces apoptosis in tamoxifen-resistant breast cancer cells. The present study demonstrated that naringenin induced an increase in ROS, resulting in oxidative stress, impaired mitochondrial function, and apoptosis in tamoxifen-resistant breast cancer cells. Our study reports that naringenin specifically increases mitochondrial superoxide anions and hydrogen peroxide production while also causing mitochondrial dysfunction. These studies provide novel evidence for the mechanism by which naringenin induces apoptosis in tamoxifen-resistant breast cancer cells and supports the use of naringenin as a therapeutic on breast cancer cells and drug-resistant cancer cells.